Postnatal growth and short-term complications in very low birth weight neonates receiving total parenteral nutrition - Purkayastha, Jayashree; Soundaram, V; Lewis, Leslie Edward; Bhat, Y Ramesh (Indian Journal of Child Health, 2016)
Objective: To study the postnatal growth and short-term complications in very low birth weight preterm neonates receiving total parenteral nutrition (TPN). Methods: This prospective, observational study was conducted in the neonatal intensive care unit of a tertiary care hospital in South India. All neonates with birth weight